Species III - Dwiggins, David; Mancuso, Frank Jr; Ripley, Ben; Feldman, Dennis; Turner, Brad; Dunne, Robin; Knepper, Rober,t; Cooke, Amelia; Pitoc, J.P; Warren, Michael; Neame, Christopher; Henstridge, Natasha; et al. (2005)
The mating game gets deadly. In the ongoing fight for supremacy between mankind and the human-alien hybrids, a fatal hybrid weakness has given humans the advantage. Until now. When Eve gives birth to Sara, she develops into the most perfect alien form.